Plan de implementación del sistema de gestión de calidad basado en la norma NTC ISO 9001:2015 en una empresa del sector servicio (2017)
This paper presents the implementation plan of the quality management system based on the requirements of the standard NTC ISO 9001: 2015 in a company in the service sector, dedicated to providing correspondent banking services to financial entities duly authorized by the financial superintendence. , consultancy and services for the cooperative and financial sector in Colombia. To start, the analysis of the context of the organization is carried out by means of the PESTAL and SWOT tool. Next, the diagnosis with respect to the fulfillment of the requirements of the norm NTC ISO 9001: 2015 is presented.